2017
DOI: 10.5334/labphon.94
|View full text |Cite
|
Sign up to set email alerts
|

West African languages enrich the frequency code: Multi-functional pitch and multi-dimensional prosody in Ikaan polar questions

Abstract: Cross-linguistically, statements tend to be pronounced with low or falling pitch and questions with high or rising pitch, a form-meaning pairing which has been attributed to the frequency code (Ohala, 1984). In many West African languages, however, questions are marked with a 'lax' prosody comprising falling intonation, low tones, lengthening, breathy termination, and open vowels ( Rialland, 2007). This paper presents prosody findings from Ikaan (Niger-Congo; ISO 639-3: kcf) and proposes a re-analysis of the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our own previous work on American English identified two roles relevant to the functions reported below: a role for breathy voice in marking "interpolated, meta-and high-priority utterances" [17], and a role in indicating dissatisfaction [18], although follow-up work found that breathy voice over about 3 seconds, with a short halfsecond excursion to non-breathy voice, was a better indicator of the latter (J. Avila, personal communication). Also relevant to our discussion below is the involvement of breathy voice in various kinds of questions in several languages: confirmation requests in Lachixío [19], polar questions in Ikaan [20], and rhetorical questions in German [21].…”
Section: Related Workmentioning
confidence: 99%
“…Our own previous work on American English identified two roles relevant to the functions reported below: a role for breathy voice in marking "interpolated, meta-and high-priority utterances" [17], and a role in indicating dissatisfaction [18], although follow-up work found that breathy voice over about 3 seconds, with a short halfsecond excursion to non-breathy voice, was a better indicator of the latter (J. Avila, personal communication). Also relevant to our discussion below is the involvement of breathy voice in various kinds of questions in several languages: confirmation requests in Lachixío [19], polar questions in Ikaan [20], and rhetorical questions in German [21].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the final vowel of YNQs is not characterized by an intensity decrease, which would be expected for lax voice but by an intensity increase [8], [12]. Based on their empirical findings [8] and [12] broach the issue of the adequacy of the categories lax and tense in [1] and [2]'s classification; see also [6]. [8] and [12] propose that final lengthening and the final fall in YNQs are not caused by lax voice but rather induced by tonal crowding due to an additional tonal target (L%) at the right edge of the utterance.…”
Section: Akan Language Backgroundmentioning
confidence: 99%
“…Out of the 6 languages of [5]'s sample only Chumburung and Deg can be described as terminating breathy. [6] shows for Ikaan, a West African Benue-Congo language of the Niger-Congo phylum spoken in Nigeria, that it uses final lengthening, breathy phonation plus voicelessness, a larger final F0 fall in combination with pitchregister raising. She further observes that intensity is overall higher in questions and mentions that intensity is not easy to integrate into the lax/tense distinction since it is not modulated by laryngeal settings.…”
Section: Introductionmentioning
confidence: 99%
“…While the arbitrary relationship between linguistic form and function is a founding principle of linguistics as a broader field (Saussure, 1916), there has long been interest in cases of apparent non-arbitrary meaning in language, and arguably a resurgence of interest in the last decade (e.g., Eckert, 2010;D'Onofrio, 2014;Podesva, Callier, Voigt, & Hilton, 2015;Pratt, 2018;Salffner, 2017;Kawahara, Noto, & Kumagai, 2018;Wong & Kang, 2019). The most iconic example of non-arbitrary meaning is codified in Ohala's Frequency Code (1984, 1994; see also Morton, 1977): Noises made by smaller things have higher frequencies than noises made by larger things, and through this fact of the physical world, higher pitch non-arbitrarily signals smallness and attributes associated with smallness, including deference and politeness (Ohala, 1994, p. 327).…”
Section: Introductionmentioning
confidence: 99%